Exploring Awareness of Learning Disabilities Among Children - Dr. Abdul Malik Abbasi (University of Chitral Journal of Linguistics and Literature)
The study aims to explore the awareness of parents-teachers regarding linguistic disabilities among children. It further hypothesizes that both parents and teachers have no awareness in terms of learning disabilities among children. These disorders refer to dyslexia, dysgraphia, dyscalculia, auditory, and the autism spectrum. Children with these disorders struggle in learning basic skills such as reading, writing, mathematics, spelling, and speech that cannot be dispensed with mental handicaps, sensory shortfalls, and emotional disturbances. These children are generally classified as slow, behind, incapable, and failures. Most importantly, autism spectrum disorder has become the order of the day among children. This is a developmental disorder caused by differences in children’s brain patterning. Additionally, the study focuses on to what extent parents, teachers, and school heads are aware and how they can help minimize these issues. For this, a mixed-method design was utilized to investigate learning disabilities among children and how these can be overcome. The primary data were collected founded on focused interview groups with parents and teachers coupled with the responses constructed on a questionnaire with multiple choices containing 30 statements. The sampling size (N=22) was taken from different universities in Sindh that were highly educated-cum-experienced parents, doctors, professors, and schoolteachers. The findings of the study reveal that the teachers and parents had inadequate awareness of children’s learning disabilities. It has been recommended that parents and teachers should be educated through different platforms for the diagnostic analysis of children with learning disabilities to offer their children a right to learn linguistic skills.